R. v. Kapp: A Case of Unfulfilled Potential - Nouvet, Dominique (Indigenous Law Journal, 2010)
Dominique Nouvet is an associate at Woodward + Company who specializes in Aboriginal law. She and her co-counsel, Robert Janes, intervened in Kapp at the Supreme Court of Canada on behalf of the T'Sou-ke, Beecher Bay, Songhees, Malahat and Snaw-naw-as First Nations. The views expressed herein are entirely her own. The Supreme Court of Canada's judgment in R. v. Kapp1 was a much anticipated decision for followers of equality and Aboriginal rights jurisprudence alike. The following commentary focuses on the Aboriginal rights implications of Kapp.